2019
DOI: 10.1055/a-0895-6046
|View full text |Cite
|
Sign up to set email alerts
|

Ablative Verfahren in der Therapie von Lebermetastasen

Abstract: ZusammenfassungWenn keine extrahepatischen Metastasen vorliegen, kann ein verbessertes Überleben mit chirurgischen und interventionellen Techniken erreicht werden. Interventionelle Techniken sind entweder definiert als perkutane oder intraoperative Laparoskopie bzw. die Anwendung von thermischer Ablation. In diesem Review konzentrieren wir uns hierbei auf die beiden etablierten Techniken der Radiofrequenzablation (RFA) und der Mikrowellenablation (MWA) zur Therapie von kolorektalen Lebermetastasen. Diese beide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Consequently, accelerated rehabilitation nursing programmes have achieved remarkable results in terms of physiological and psychological well-being of patients, and relieving family pressures. 47 Our results showed that accelerated rehabilitation nursing programmes are effective in reducing the incidence of surgical site wound infections among patients undergoing LC. Compared with previous assessments, although this evaluation summarised the available evidence on the effect of accelerated rehabilitation nursing programmes on surgical site wound infection in patients undergoing LC, there are still limitations that need to be addressed: (1) The high heterogeneity of indicators affected the accuracy of the evaluation results; (2) The specific implementation measures of accelerated rehabilitation nursing programmes do not have standardised criteria.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Consequently, accelerated rehabilitation nursing programmes have achieved remarkable results in terms of physiological and psychological well-being of patients, and relieving family pressures. 47 Our results showed that accelerated rehabilitation nursing programmes are effective in reducing the incidence of surgical site wound infections among patients undergoing LC. Compared with previous assessments, although this evaluation summarised the available evidence on the effect of accelerated rehabilitation nursing programmes on surgical site wound infection in patients undergoing LC, there are still limitations that need to be addressed: (1) The high heterogeneity of indicators affected the accuracy of the evaluation results; (2) The specific implementation measures of accelerated rehabilitation nursing programmes do not have standardised criteria.…”
Section: Discussionmentioning
confidence: 59%
“…Consequently, accelerated rehabilitation nursing programmes have achieved remarkable results in terms of physiological and psychological well‐being of patients, and relieving family pressures. 47 Our results showed that accelerated rehabilitation nursing programmes are effective in reducing the incidence of surgical site wound infections among patients undergoing LC.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation